High resolution analysis of genes transcribed in Ixodid tick tissues with special reference to salivary glands of the brown ear tick, Rhipicephalus appendiculatus - De Villiers, Etienne (University of Pretoria, 2014)
Thesis (PhD)--University of Pretoria, 2013.